Does Late Hip Dysplasia Occur After Normal Ultrasound Screening in Breech Babies?. Issue 4 (April 2019) - Morris, Andrew R.; Thomas, Joanna M.C.; Reading, Isabel C.; Clarke, Nicholas M.P.
Abstract : Background: Recent literature has raised concern regarding the occurrence of late dysplasia after normal screening in breech babies. One paper states a late dysplasia incidence of 29%. This finding is in contrast with other published work, which suggests breech presentation is predictive of spontaneous stabilization of the unstable neonatal hip. We decided to identify the rate of late dysplasia after normal screening in our patient cohort and also to investigate the use of a prophylactic abduction diaper. Methods: During the study period of December 2012 to June 2014, breech babies referred to the screening program at our institution were identified. Ninety babies were prospectively enrolled into the study and randomized to either the observational arm or prophylactic treatment with the Healthy Hip Diaper (HALO, Minnetonka, MN). All babies had a normal initial clinical examination and ultrasound. Regular follow-up including clinical and ultrasound examination was undertaken culminating in pelvic x-rays performed at 13±1 months. A total of 63% of patients elected against their randomization to prophylactic treatment, 28% opted for prophylactic treatment against their randomization to observation only, meaning a total of 40% of babies proceeded against their initial randomization. In total, 75% of recruited babies completed follow-up. Dysplasia was defined as an acetabular index >2 SD from the mean sex, age, and side-specific values. Results: The overall rate of radiographic dysplasia at 13 months was 7.4%. The rate was 5% in those using a Healthy Hip Diaper and 8.3% in those under observation only. This was not a statistically significant difference. Two patients required operative intervention, one requiring capsulorraphy with acetabuloplasty, the other requiring an arthrogram. Overall compliance with the abduction diaper was low. Conclusions: We conclude that late radiographic dysplasia does occur after normal clinical and ultrasound screening in breech babies, although not to the same extent as recently published data. We cannot recommend prophylactic abduction devices for breech babies who have a normal hip ultrasound at 6 weeks of age. Consideration must be given to further clinical and radiographic follow-up for hip dysplasia when the risk factor of breech presentation is present. Level of Evidence: Level II—prospective comparative trial.